National Addiction-specific Institutional Infrastructure - fundamental prerequisite for successful implementation of specialized academic degree study programmes: a case study in historical perspective - Miovský, Michal; Vondrová, Anna; Peters, Roger; Kathungu, Beatrice; Lososová, Amalie (Central European Journal of Public Health, 2019)
OBJECTIVE: Human resources are crucial for addiction treatment and prevention services, as well as for science and research. The aim of this historical case study is to explain and demonstrate the role of specialized university academic degree study programmes in addictions in the context of a national institutional infrastructure. This specific group of very highly specialized academic programmes represents the highest level of professional development and is producing a totally new generation of addiction specialists with a very distinctive professional identity. METHODS: The study protocol is based on a case study research design and the case is defined as the historical development of addiction specialized institutions closely related to self-help, prevention, and treatment activities on the historical territory of the Czech Republic. We identified relevant historical sources related to establishing and/or running activities or institutions according to the categories specified in our concept of the national institutional infrastructure. All the materials and sources that were collected were sorted according to a timeline and categories of institutions and we systematically determined the first recorded activity/institution in each particular category. For this simple sorting system we used open and selected coding according to Grounded Theory. RESULTS: The public health model developed by Thomas Babor recognizes six different structural mechanisms to support university-based programmes in addiction studies: specialized journals, research centres, professional societies, specialized libraries and documentation centres, training and education programmes and institutions, and funding agencies. We attempted to redefine the concept of addiction studies within the broader context of the addiction field and added three additional mechanisms of support: public interest groups, self-help groups, and service providers. Using a historical case study in the Czech Republic, we demonstrate the potential for a broader context and interaction between these support mechanisms and academic institutions hosting academic programmes in addiction studies. CONCLUSION: The process of establishing integrated addiction studies programmes at Charles University in the Czech Republic had its origins in, and support from, various national institutions and professional organizations. This allowed the university to develop academic programmes at the bachelor's, master's, and Ph.D. levels. The availability of career opportunities for advanced-level addiction professionals in the Czech Republic was also a critically important factor in developing sustainable academic programmes in addiction studies. Our experience is that the creation of successful and sustainable academic programmes for addiction professionals is difficult to achieve without broad infrastructure support, national advocacy efforts, and legislative change at the national level.
Keywords: Education, Medical; History, 21st Century; případové studie organizací; Česká republika; Addiction Medicine; Organizational Case Studies; hodnocení programu; lidé; adiktologie; studium lékařství; Program Evaluation; Czech Republic; dějiny 21. století; Humans